Coinitiator-added gold nanocluster photoresist and method
By adding thiol or amine as co-initiator to the gold nanocluster photoresist, the problem of low processing sensitivity of existing two-photon 3D printing materials is solved, and the effect of efficient processing of complex 3D structures and ultraviolet patterning is achieved.
Patent Information
- Application Number
- CN202510054152.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The existing two-photon 3D printing materials have low processing sensitivity, insufficient structural mechanical properties, and it is difficult to achieve high-throughput printing of complex three-dimensional structures at low power.
The gold nanocluster photoresist with co-initiator is used to improve the initiation and processing performance of the photoresist by adding thiol or amine to the gold nanocluster photoresist.
It achieves extremely high processing sensitivity and extremely low processing thresholds, can efficiently process complex 3D structures and realize light patterning under ultraviolet light conditions.
Smart Images

Figure CN119861532A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of micro-nano processing and photosensitive materials, and specifically relates to a gold nanocluster two-photon photoresist with added co-initiator and a micro-nano 3D printing and photo-patterning method thereof. Background Art
[0002] Two-photon 3D printing, also known as micro-nano 3D printing, is the most representative micro-nano 3D printing technology in the 21st century. This technology has unique advantages such as ultra-high three-dimensional precision and powerful three-dimensional molding capabilities. Two-photon printing is essentially a three-dimensional writing technology; it does not require the creation of complex objects layer by layer, and can create microstructures with submicron feature sizes in a relatively simple way. These characteristics stem from the nonlinear optical properties of light absorption in two-photon 3D printing and the subsequent polymerization chemistry. Unlike traditional single-photon polymerization, in the two-photon printing process, two photons are absorbed by the photosensitive material at the same time. The total energy from the two photons resonates with the energy difference between the ground state and the excited state. Due to the nonlinear absorption characteristics that occur in this process, two-photon printing has higher resolution than single-photon polymerization.
[0003] However, most of the materials used for two-photon 3D printing are two-photon photoresists composed of organic resin monomers and organic small molecule initiators. The initiator content is low, the processing sensitivity is low, and the mechanical properties of the processed structure are low. The use of metal-polymer composite materials can significantly improve the mechanical properties of 3D structures. At present, metal ions or inorganic nanoparticles can be added to the photoresist and the 3D structure of organic-inorganic composite materials can be obtained by two-photon 3D printing; it can also be achieved by evaporating a layer of metal on the organic three-dimensional structure. However, these methods have disadvantages such as low processing accuracy, complex steps or single processing structure.
[0004] Under laser, due to the presence of inorganic nanoparticles, the strong light scattering effect will reduce the 3D printing resolution, and it is difficult to effectively control the processing accuracy of the structure by two-photon 3D printing through two-photon reduction of metal ions. The technical literature (QiLi, et al. Mechanical nanolattices printed using nanocluster-based photoresists, Science. 2022) developed gold / silver metal nanocluster-based two-photon photoresist for the first time. This ultra-small size of metal nanoclusters will not cause light scattering and lead to reduced 3D structure resolution. Metal nanoclusters have good solubility in polymerization active monomers, and can realize the "one-step" 3D printing of organic-inorganic composite materials without complicated post-processing. The technical literature (Jin Tang, et al. Two-Orders-of-Magnitude Enhancement of Photoinitiation Activity via a Simple Surface Engineering of Metal Nanoclusters, Angew. Chem. Int. Ed. 2024) obtained a cluster two-photon photoresist with higher sensitivity, but due to its high concentration and low transmittance, it cannot meet the needs of high-throughput two-photon 3D printing of complex three-dimensional structures at low power.
[0005] Photoinitiators are divided into Type I and Type II. Type I initiators generate free radicals by breaking the chemical bonds inside the molecule under light conditions, thereby initiating subsequent chemical reactions. Type II initiators generate free radicals by absorbing hydrogen, and are usually used together with hydrogen proton donors (coinitiators). Usually, Type II initiators will have a significant improvement in initiation performance after adding co-initiators. Traditional small molecule Type II co-initiators will have a significant improvement in two-photon initiation performance after adding amines, but no significant improvement in initiation performance was found after adding thiols. The gold nanoclusters invented this time are the first type II cluster initiators discovered. Unlike traditional organic small molecule photoinitiators, not only will there be a significant improvement after adding amines, but the improvement in initiation performance is even greater after adding thiols. The printing sensitivity has reached an extremely high level, and it has excellent processability. Summary of the invention
[0006] The object of the present invention is to overcome the defects in the prior art and provide a gold nanocluster photoresist and method to which a co-initiator (thiol or amine) is added. The present invention is based on micro-nano 3D printing of a gold nanocluster photoresist to which a co-initiator is added. The method can complete the printing of a 3D structure in one step, and has extremely high sensitivity, extremely low processing threshold, and excellent solubility and processing performance. In addition, based on the photocuring performance of the gold nanocluster photoresist to which a co-initiator is added under ultraviolet light, the method of the present invention realizes the first photopatterning under ultraviolet light conditions using gold nanoclusters as photoinitiators.
[0007] The specific technical solutions adopted by the present invention are as follows:
[0008] In a first aspect, the present invention provides a gold nanocluster photoresist with added co-initiator, comprising, calculated by mass percentage, 0.01wt%-30wt% of gold nanoclusters, 1wt%-10wt% of co-initiator, 95wt%-70wt% of polymerization active monomers, and 0.1wt%-5wt% of organic solvent.
[0009] Preferably, the gold nanoclusters are Au 25 (SC8H 17 ) 18 ,Au 25 (SC 10 H 21 ) 18 ,[Au 25 (PPh3) 10 (SC8H 17 )5] 2+ ,Au 25 (SC6H 12 OH) 18 ,Au 25 (SC3H6) 18 ,[Au 25 (PPh3) 10 (SC3H6)5] 2+ ,[Au 25 (PPh3) 10 (SC6H 12 OH)5] 2+ ,Au 25 (SC2H4Ph) 18 ,Au 25 (SCH2Ph) 18 ,Au 25 (SC6H 13 ) 18 Any one or a combination of two or more.
[0010] Preferably, the co-initiator is a thiol or an amine; the thiol is benzenethiol, benzylthiol, phenylethiol, phenylpropylthiol, butylthiol, pentanethiol, hexanethiol, octanethiol, nonanethiol, decanethiol, cyclohexanethiol, adamantanethiol, pentaerythritol tetrakis(3-mercaptopropionic acid) ester, p-phenylenedithiol, m-phenylenedithiol, o-phenylenedithiol, p-phenylmethylthiol, m-phenylmethylthiol, o-phenylmethylthiol, p-phenylenedithiol, m-phenylmethylthiol, o-phenylmethylthiol, p-phenylenedithiol, m-phenylenedithiol, The amine is any one of aniline, benzylamine, phenylethylamine, amphetamine, triethylamine, butylamine, pentylamine, hexylamine, octylamine, nonylthiolamine, decylamine, cyclohexylamine, p-phenylenediamine, m-phenylenediamine, o-phenylenediamine, p-benzylamine, m-benzylamine, o-benzylamine, p-phenylenediamine, o-phenylenediamine, m-phenylenediamine and hexylenediamine, or a combination of two or more thereof.
[0011] Preferably, the polymerization active monomer is any one of polyethylene glycol diacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, trimethylolpropane triacrylate, polydipentaerythritol pentaacrylate, acrylic-cage polysilsesquioxane, neopentyl glycol diacrylate, dipentaerythritol hexaacrylate and diurethane dimethacrylate, or a combination of two or more thereof.
[0012] Preferably, the organic solvent is any one of methanol, ethanol, isopropanol, ethyl ether, diethanol monomethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, propylene glycol methyl ether acetate, γ-butyrolactone, di(ethylene glycol) diethyl ether, methyl isobutyl ketone diethanol monoethyl ether, acetone, dichloromethane, chloroform, n-hexane, toluene, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide, or a combination of two or more thereof.
[0013] In a second aspect, the present invention provides a method for preparing a gold nanocluster photoresist with a co-initiator added, as follows:
[0014] 0.01wt%-30wt% of gold nanoclusters calculated by mass percentage and 1wt%-5wt% of organic solvent are uniformly mixed, and then 95wt%-70wt% of polymerization active monomers calculated by mass percentage are added, and finally 1wt%-10wt% of coinitiator calculated by mass percentage is added, and the mixed solution is stirred and dispersed for 5-30 minutes to obtain a gold nanocluster photoresist with added coinitiator.
[0015] In a third aspect, the present invention provides a micro-nano 3D printing method based on a gold nanocluster photoresist with the addition of a co-initiator, as follows:
[0016] The gold nanocluster photoresist with added coinitiator as described in any one of the first aspects or the gold nanocluster photoresist with added coinitiator obtained by the preparation method described in the second aspect is 3D printed by a two-photon 3D printing system; the obtained 3D structure is then developed in a developer and blown dry with nitrogen to obtain the 3D structure of the gold nanocluster photoresist with added coinitiator.
[0017] Preferably, in the two-photon 3D printing system, the laser wavelength is 780 nm, the laser power is 0.25-50 mW, the laser pulse is 120 fs, the laser frequency is 80 MHz, and the printing speed is 0.1-100 mm / s.
[0018] Preferably, the developer is any one of propylene glycol methyl ether acetate, isopropyl alcohol, and dichloromethane, or a combination of two or more thereof, and the developing time is 2-40 minutes.
[0019] In a fourth aspect, the present invention provides a 3D structure of a gold nanocluster photoresist with a co-initiator added, prepared by the micro-nano 3D printing method as described in the third aspect.
[0020] In the fifth aspect, the present invention provides an application of a gold nanocluster photoresist with an added co-initiator in photopatterning. Specifically, a gold nanocluster photoresist with an added co-initiator as described in any one of the first aspects or a gold nanocluster photoresist with an added co-initiator obtained by the preparation method described in the second aspect is placed in a mold and cured under an ultraviolet light source with a wavelength of 365nm.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The gold nanocluster photoresist with added co-initiator prepared by the present invention uses gold nanoclusters as initiators and thiols or amines as co-initiators. It has excellent processing performance (extremely high processing sensitivity and extremely low processing threshold), can process a variety of complex 3D structures, and can achieve photopatterning under ultraviolet light conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is an electron microscope image of the three-dimensional structure of the photoresist obtained in Example 1 after micro-nano 3D printing.
[0024] Figure 2 This is an optical microscope image of the block structure of the photoresist obtained in Example 1 after micro-nano 3D printing.
[0025] Figure 3 This is an optical microscopy image of the three-dimensional structure of the photoresist obtained in Example 2 after micro-nano 3D printing.
[0026] Figure 4This is an optical microscopy image of the block structure of the photoresist obtained in Example 3 after micro-nano 3D printing.
[0027] Figure 5 This is an optical microscope image of the frame structure of the photoresist obtained in Example 4 after micro-nano 3D printing.
[0028] Figure 6 This is an optical microscope image of the frame structure of the photoresist obtained in Example 5 after micro-nano 3D printing.
[0029] Figure 7 This is an optical microscope image of the frame structure of the photoresist obtained in Example 6 after micro-nano 3D printing.
[0030] Figure 8 This is a photograph of the photoresist obtained in Example 1 after being cured by ultraviolet light. DETAILED DESCRIPTION
[0031] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. However, it should be understood by those skilled in the art that these embodiments are only used as cases. The numerous variations, changes and substitutions that can be thought of by those skilled in the art at present do not exceed the present invention. It should be understood that various replacements made to the embodiments of the present invention described in this application document can be adopted in the practice of the present invention. The attached claims are intended to limit the scope of the present invention, and the methods and structures within the scope of these claims and their equivalents should be covered thereby. For those who do not specify specific conditions in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments involved without indicating the manufacturer are all conventional products available through commercial purchase.
[0032] First, the present invention provides a gold nanocluster photoresist with added co-initiator, the composition of the material mainly includes (calculated by mass percentage): 0.01wt%-30wt% of gold nanoclusters, 1wt%-10wt% of co-initiator, 95wt%-70wt% of polymerization active monomers and 0.1wt%-5wt% of organic solvent.
[0033] As a preferred embodiment of the present invention, the gold nanoclusters can be Au 25 (SC8H 17 ) 18 ,Au 25 (SC 10 H 21 ) 18 ,[Au 25 (PPh3) 10 (SC8H 17 )5] 2+ ,Au 25 (SC6H 12OH) 18 ,Au 25 (SC3H6) 18 ,[Au 25 (PPh3) 10 (SC3H6)5] 2+ ,[Au 25 (PPh3) 10 (SC6H 12 OH)5] 2 ,Au 25 (SC2H4Ph) 18 ,Au 25 (SCH2Ph) 18 and Au 25 (SC6H 13 ) 18 The co-initiator may be a thiol or an amine. Wherein, the thiol is any one of benzenethiol, benzylthiol, phenylethylthiol, phenylpropylthiol, butylamine, pentylthiol, hexylthiol, octylthiol, nonylthiol, decylthiol, cyclohexylthiol, adamantanethiol, pentaerythritol tetrakis(3-mercaptopropionic acid) ester, p-phenylenedithiol, m-phenylenedithiol, o-phenylenedithiol, p-phenylmethylthiol, m-phenylmethylthiol, o-phenylmethylthiol, p-phenylenedithiol, m-phenylenedithiol, o-phenylmethylthiol and hexylenedithiol, or a combination of two or more thereof; the amine is any one of aniline, benzylamine, phenylethylamine, amphetamine, triethylamine, butylamine, pentylamine, hexylamine, octylamine, nonylthiolamine, decylamine, cyclohexylamine, p-phenylenediamine, m-phenylenediamine, o-phenylenediamine, p-benzylamine, m-benzylamine, o-benzylamine, p-phenylenediamine, o-phenylenediamine, m-phenylenediamine and hexylenediamine, or a combination of two or more thereof. The polymerization active monomer can be any one of polyethylene glycol diacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, trimethylolpropane triacrylate, polydipentaerythritol pentaacrylate, acrylic-cage polysilsesquioxane, neopentyl glycol diacrylate, dipentaerythritol hexaacrylate and diurethane dimethacrylate, or a combination of two or more thereof. The organic solvent can be any one of ether, diethanol monomethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, propylene glycol methyl ether acetate, γ-butyrolactone, di(ethylene glycol) diethyl ether, methyl isobutyl ketone diethanol monoethyl ether, acetone, dichloromethane, chloroform, n-hexane, toluene, tetrahydrofuran, N,N-dimethylformamide methanol, ethanol and isopropanol, or a mixture of two or more thereof.
[0034] Secondly, for the above-mentioned gold nano cluster photoresist of adding mercaptan, it can be obtained by uniformly mixing the components. Specifically, in the preparation process, 0.01wt%-30wt% of gold nano clusters calculated by mass percentage content and 0.1wt%-5wt% of organic solvent can be uniformly mixed first, then 95wt%-70wt% of polymerization active monomer calculated by mass percentage content is added, stirred and dispersed (preferably the ultrasonic dispersion time is 5-30min), and finally 1wt%-10wt% of mercaptan calculated by mass percentage content is dripped to obtain the gold nano cluster photoresist of adding mercaptan. For the above-mentioned gold nano cluster photoresist of adding amine, it can be obtained by uniformly mixing the components. Specifically, during the preparation process, 0.01wt%-30wt% of gold nanoclusters calculated by mass percentage and 0.1wt%-5wt% of organic solvent can be uniformly mixed first, and then 95wt%-70wt% of polymerization active monomers calculated by mass percentage are added, stirred and dispersed (preferably the ultrasonic dispersion time is 5-30min), and finally 1wt%-10wt% of amine calculated by mass percentage is dropped to obtain a gold nanocluster photoresist with added amine.
[0035] Based on the gold nanocluster photoresist with added co-initiator, the present invention also prepares a 3D structure, and the two-photon 3D printing method (i.e., micro-nano 3D printing method) used is as follows:
[0036] The gold nanocluster photoresist with the co-initiator added is 3D printed by a two-photon 3D printing system; the obtained 3D structure is then developed in a developer and blown dry with nitrogen to obtain a 3D structure of the gold nanocluster photoresist with the co-initiator added.
[0037] As a preferred embodiment of the present invention, during the operation of the two-photon 3D printing system, the laser wavelength is set to 780nm, the laser power is set to 0.25-50mW, the laser pulse is set to 120fs, the laser frequency is set to 80MHz, and the printing speed is set to 0.1-100mm / s.
[0038] As a preferred embodiment of the present invention, the developer is preferably any one of propylene glycol methyl ether acetate, isopropyl alcohol, and dichloromethane, or a mixture of two or more thereof, and the developing time is 2-40 minutes.
[0039] Finally, based on the gold nanocluster photoresist with added coinitiator, the present invention also realizes photopatterning by ultraviolet light irradiation, and the specific implementation method is as follows:
[0040] The gold nanocluster photoresist with co-initiator added was dripped into the mold and the wavelength was 365nm and the power was 1W / cm 2 The photocured polymer pattern can be obtained by irradiating with ultraviolet light for 3 to 5 minutes.
[0041] In the present invention, the gold nanoclusters with added co-initiators have high initiation performance, and the photoresist has excellent processing performance (extremely high processing sensitivity and extremely low processing threshold), realizing the "one-step" processing of metal-polymer 3D structures, and realizing the photo-patterning of metal-polymers for the first time.
[0042] The method and effects of the present invention will be specifically described below through examples.
[0043] Example 1
[0044] Take 1 mg Au 25 (SC2H4Ph) 18 In 20 μL of dichloromethane, ultrasonic dispersion was performed for 2 minutes, and then 99 mg of pentaerythritol triacrylate was added, and then 5 μL of phenylethyl mercaptan was added, and stirred and dispersed at room temperature for 5 minutes to obtain a gold nanocluster photoresist with phenylethyl mercaptan added.
[0045] Example 2
[0046] Take 1 mg Au 25 (SC2H4Ph) 18 Ultrasonic dispersion was performed in 20 μL of dichloromethane for 2 min, and then 99 mg of pentaerythritol triacrylate was added, followed by 5 μL of benzyl mercaptan, and the mixture was stirred and dispersed at room temperature for 5 min to obtain a gold nanocluster photoresist with benzyl mercaptan added.
[0047] Example 3
[0048] Take 1 mg Au 25 (SC2H4Ph) 18 In 20 μL of dichloromethane, ultrasonic dispersion was performed for 2 minutes, and then 99 mg of pentaerythritol triacrylate was added, and then 5 μL of phenylethylamine was added, and stirred and dispersed at room temperature for 5 minutes to obtain a gold nanocluster photoresist with phenylethylamine added.
[0049] Example 4
[0050] Take 1 mg Au 25 (SC2H4Ph) 18 In 20 μL of dichloromethane, ultrasonic dispersion was performed for 2 minutes, and then 99 mg of pentaerythritol triacrylate was added, and then 5 μL of benzylamine was added, and the mixture was stirred and dispersed at room temperature for 5 minutes to obtain a gold nanocluster photoresist with benzylamine added.
[0051] Example 5
[0052] Take 1 mg Au 25 (SCH2Ph) 18In 20 μL of dichloromethane, ultrasonic dispersion was performed for 2 minutes, and then 99 mg of pentaerythritol triacrylate was added, and then 5 μL of phenylethyl mercaptan was added, and stirred and dispersed at room temperature for 5 minutes to obtain a gold nanocluster photoresist with phenylethyl mercaptan added.
[0053] Example 6
[0054] Take 1 mg Au 25 (SCH2Ph) 18 In 20 μL of dichloromethane, ultrasonic dispersion was performed for 2 minutes, and then 99 mg of pentaerythritol triacrylate was added, and then 5 μL of benzyl mercaptan was added, and stirred and dispersed at room temperature for 5 minutes to obtain a gold nanocluster photoresist with benzyl mercaptan added.
[0055] Example 7
[0056] In a light-proof environment, an appropriate amount of the gold nanocluster photoresist with thiol (phenylethyl mercaptan) added obtained in Example 1 was smeared on a glass slide, and 3D printing was performed under a 780nm titanium sapphire femtosecond laser, with a femtosecond laser pulse of 120fs, a laser frequency of 80MHz, a laser power of 1mW, and a printing speed of 5mm / s to obtain the following Figure 1 As shown in the figure, the structure processed using the material obtained in Example 1 has a stable three-dimensional morphology.
[0057] Example 8
[0058] In a light-proof environment, an appropriate amount of the gold nanocluster photoresist with thiol (phenylethyl mercaptan) added obtained in Example 1 was smeared on a glass slide, and 3D printing was performed under a 780nm titanium sapphire femtosecond laser, with a femtosecond laser pulse of 120fs, a laser frequency of 80MHz, scanning rates of 5, 10, 30, 50, 70, 90, and 110mm / s, respectively, and laser powers of 0.25, 0.5, 0.75, and 1.0mW, respectively, to obtain the following: Figure 2 The three-dimensional square structure shown in the figure. As can be seen from the figure, the square structure collapsed, which is because the printing laser power is very low and the structure is not fully polymerized. This ultra-low laser power shows that the gold nanocluster photoresist with added thiol has an ultra-low polymerization threshold and ultra-high sensitivity.
[0059] Example 9
[0060] In a light-proof environment, an appropriate amount of the gold nanocluster photoresist with thiol (benzyl mercaptan) added obtained in Example 2 was smeared on a glass slide, and 3D printing was performed under a 780nm titanium sapphire femtosecond laser, with a femtosecond laser pulse of 120fs, a laser frequency of 80MHz, scanning rates of 5, 10, 30, 50, 70, 90, and 110mm / s, respectively, and laser powers of 0.3, 0.4, 0.5, and 0.6mW, respectively, to obtain the following: Figure 3The three-dimensional structure shown in the figure. As can be seen from the figure, the square structure collapsed, which is because the printing laser power is very low and the structure is not fully polymerized. This ultra-low laser power shows that the gold nanocluster photoresist with added thiol has an ultra-low polymerization threshold and ultra-high sensitivity.
[0061] Example 10
[0062] In a light-proof environment, an appropriate amount of the gold nanocluster photoresist with amine (phenylethylamine) added obtained in Example 3 was smeared on a glass slide, and 3D printing was performed under a 780nm titanium sapphire femtosecond laser, with a femtosecond laser pulse of 120fs, a laser frequency of 80MHz, scanning rates of 5, 10, 30, 50, 70, 90, and 110mm / s, respectively, and laser powers of 0.2, 0.4, and 0.6mW, respectively, to obtain the following: Figure 4 The three-dimensional structure shown in the figure. As can be seen from the figure, the square structure collapsed, which is because the printing laser power is very low and the structure is not fully polymerized. This ultra-low laser power shows that the gold nanocluster photoresist with added amine has an ultra-low polymerization threshold and ultra-high sensitivity.
[0063] Embodiment 11
[0064] In a light-proof environment, an appropriate amount of the gold nanocluster photoresist with amine (benzylamine) added obtained in Example 4 was smeared on a glass slide, and 3D printing was performed under a 780nm titanium sapphire femtosecond laser, with a femtosecond laser pulse of 120fs, a laser frequency of 80MHz, a scanning rate of 5, 10, 30, 50, 70, 90, and 110mm / s, and a laser power of 0.5, 1.0, and 1.5mW, respectively, to obtain the following: Figure 5 The three-dimensional structure shown in the figure. As can be seen from the figure, the square structure collapsed, which is because the printing laser power is very low and the structure is not fully polymerized. This ultra-low laser power shows that the gold nanocluster photoresist with added amine has an ultra-low polymerization threshold and ultra-high sensitivity.
[0065] Example 12
[0066] In a light-proof environment, an appropriate amount of the gold nanocluster photoresist with thiol (phenylethyl mercaptan) added obtained in Example 5 was smeared on a glass slide, and 3D printing was performed under a 780nm titanium sapphire femtosecond laser, with a femtosecond laser pulse of 120fs, a laser frequency of 80MHz, a scanning rate of 5, 10, 30, 50, 70, 90, and 110mm / s, and a laser power of 1, 2, 3, 4, and 5mW, respectively, to obtain the following Figure 6 The three-dimensional structure shown in the figure. As can be seen from the figure, the square structure collapsed, which is because the printing laser power is very low and the structure is not fully polymerized. This ultra-low laser power shows that the gold nanocluster photoresist with added thiol has an ultra-low polymerization threshold and ultra-high sensitivity.
[0067] Embodiment 13
[0068] In a light-proof environment, an appropriate amount of the gold nanocluster photoresist with thiol (benzyl mercaptan) added obtained in Example 6 was smeared on a glass slide, and 3D printing was performed under a 780nm titanium sapphire femtosecond laser, with a femtosecond laser pulse of 120fs, a laser frequency of 80MHz, scanning rates of 5, 10, 30, 50, 70, 90, and 110mm / s, respectively, and laser powers of 0.5, 1, 1.5, and 2.0mW, respectively, to obtain the following: Figure 7 The three-dimensional structure shown in the figure. As can be seen from the figure, the square structure collapsed, which is because the printing laser power is very low and the structure is not fully polymerized. This ultra-low laser power shows that the gold nanocluster photoresist with added thiol has an ultra-low polymerization threshold and ultra-high sensitivity.
[0069] Embodiment 14
[0070] In a light-proof environment, take an appropriate amount of the gold nanocluster photoresist with thiol (phenylethyl mercaptan) added obtained in Example 1 and drop it into the mold, and use a wavelength of 365nm and a power of 0.03-1W / cm 2 The photoresist is cured by irradiating with ultraviolet light for 1-5 minutes. Figure 8 The solid shown in the figure emits red fluorescence, which shows that the photoresist can be polymerized under ultraviolet light to achieve photopatterning.
[0071] It can be seen that the gold nanocluster photoresist with added coinitiator of the present invention has excellent processing performance (extremely high processing sensitivity and extremely low processing threshold), can process various complex 3D structures and realize light patterning under ultraviolet light conditions. The present invention adds thiol or amine to the gold nanocluster photoresist to significantly improve the solubility and transmittance and produce a special interaction with the gold nanoclusters. The photoresist has ultra-high sensitivity, ultra-low threshold, and excellent printing effect; it can realize ultra-low power processing of metal-polymer 3D structures and can also realize ultraviolet light curing.
[0072] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A gold nanocluster photoresist with added coinitiator, characterized in that: The invention comprises 0.01wt%-30wt% of gold nano clusters, 1wt%-10wt% of a co-initiator, 95wt%-70wt% of a polymerization active monomer and 0.1wt%-5wt% of an organic solvent, calculated by mass percentage.
2. The gold nanocluster photoresist with added coinitiator according to claim 1, characterized in that: The gold nanoclusters are Au 25 (SC8H 17 ) 18 ,Au 25 (SC 10 H 21 ) 18 ,[Au 25 (PPh3) 10 (SC8H 17 )5] 2+ ,Au 25 (SC6H 12 OH) 18 ,Au 25 (SC3H6) 18 ,[Au 25 (PPh3) 10 (SC3H6)5] 2+ ,[Au 25 (PPh3) 10 (SC6H 12 OH)5] 2+ ,Au 25 (SC2H4Ph) 18 ,Au 25 (SCH2Ph) 18 ,Au 25 (SC6H 13 ) 18 Any one or a combination of two or more.
3. The gold nanocluster photoresist with added coinitiator according to claim 1, characterized in that: The co-initiator is a thiol or an amine; the thiol is benzenethiol, benzylthiol, phenylethiol, phenylpropylthiol, butylthiol, pentanethiol, hexanethiol, octanethiol, nonanethiol, decanethiol, cyclohexanethiol, adamantanethiol, pentaerythritol tetrakis(3-mercaptopropionic acid) ester, p-phenylenedithiol, m-phenylenedithiol, o-phenylenedithiol, p-phenylmethylthiol, m-phenylmethylthiol, o-phenylmethylthiol, p-phenylenedithiol, m-phenylenedithiol, Any one of o-phenylenediol and hexanedithiol or a combination of two or more thereof; the amine is any one of aniline, benzylamine, phenylethylamine, amphetamine, triethylamine, butylamine, pentylamine, hexylamine, octylamine, nonylthiolamine, decylamine, cyclohexylamine, p-phenylenediamine, m-phenylenediamine, o-phenylenediamine, p-benzylamine, m-benzylamine, o-benzylamine, p-phenylenediamine, o-phenylenediamine, m-phenylenediamine and hexylenediamine or a combination of two or more thereof.
4. The gold nanocluster photoresist with added coinitiator according to claim 1, characterized in that: The polymerization active monomer is any one of polyethylene glycol diacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, trimethylolpropane triacrylate, polydipentaerythritol pentaacrylate, acrylic-cage polysilsesquioxane, neopentyl glycol diacrylate, dipentaerythritol hexaacrylate and diurethane dimethacrylate, or a combination of two or more thereof.
5. The gold nanocluster photoresist with added coinitiator according to claim 1, characterized in that: The organic solvent is any one of methanol, ethanol, isopropanol, ethyl ether, diethanol monomethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, propylene glycol methyl ether acetate, γ-butyrolactone, di(ethylene glycol) diethyl ether, methyl isobutyl ketone diethanol monoethyl ether, acetone, dichloromethane, chloroform, n-hexane, toluene, tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide, or a combination of two or more thereof.
6. A method for preparing a gold nanocluster photoresist with a co-initiator added, characterized in that: The details are as follows: 0.01wt%-30wt% of gold nanoclusters calculated by mass percentage and 1wt%-5wt% of organic solvent are uniformly mixed, and then 95wt%-70wt% of polymerization active monomers calculated by mass percentage are added, and finally 1wt%-10wt% of coinitiator calculated by mass percentage is added, and the mixed solution is stirred and dispersed for 5-30 minutes to obtain a gold nanocluster photoresist with added coinitiator.
7. A micro-nano 3D printing method based on gold nanocluster photoresist with added co-initiator, characterized in that: The details are as follows: The gold nanocluster photoresist with added coinitiator as described in any one of claims 1 to 5 or the gold nanocluster photoresist with added coinitiator obtained by the preparation method as described in claim 6 is 3D printed by a two-photon 3D printing system; the obtained 3D structure is then developed in a developer and blown dry with nitrogen to obtain the 3D structure of the gold nanocluster photoresist with added coinitiator.
8. The micro-nano 3D printing method according to claim 7, characterized in that: In the 3D printing system, the laser wavelength is 780nm, the laser power is 0.25-50mW, the laser pulse is 120fs, the laser frequency is 80MHz, and the printing speed is 0.1-100mm / s; the developer is any one of propylene glycol methyl ether acetate, isopropyl alcohol, and dichloromethane, or a combination of two or more thereof, and the developing time is 2-40min.
9. A 3D structure of a gold nanocluster photoresist with added co-initiator prepared by the micro-nano 3D printing method as claimed in claim 7.
10. Application of a gold nanocluster photoresist with a co-initiator added in photopatterning, characterized in that: The gold nanocluster photoresist with added coinitiator as claimed in any one of claims 1 to 5 or the gold nanocluster photoresist with added coinitiator obtained by the preparation method as claimed in claim 6 is placed in a mold and cured under an ultraviolet light source with a wavelength of 365 nm.
Citation Information
Patent Citations
Nanowire-based flexible transparent conducting electrode and preparation method thereof
CN104882190A
Double-lamp-curing white UV inkjet ink and preparation method thereof
CN109957282A
Gold nanocluster two-photon photoresist protected by straight-chain thiol and micro-nano 3D printing method
CN118033977A
Cited By
Preparation method of high-conductivity PEDOT three-dimensional micro-nano structure
CN121672414A